Nonaqueous electrolyte power storage element

By using a lithium alloy with aluminum in the negative electrode and fluorinated cyclic carbonate in the electrolyte, the Li-S battery's capacity retention is enhanced through reduced overvoltage and dendrite suppression, addressing the low retention issue in Li-S batteries.

JP2025009019APending Publication Date: 2025-01-20GS YUASA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023111722
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Li-S batteries exhibit low capacity retention rates during charge/discharge cycles due to large overvoltage caused by lithium ion precipitation and dendrite formation on the negative electrode.

Method used

Incorporating a positive electrode with elemental sulfur, a negative electrode with a lithium alloy containing an aluminum element, and a non-aqueous electrolyte with fluorinated saturated cyclic carbonate, which forms a protective film on the negative electrode surface to suppress overvoltage and dendrite growth.

Benefits of technology

The solution results in a non-aqueous electrolyte storage device with a high capacity retention rate during charge/discharge cycles by maintaining the lithium alloy's crystal structure and preventing dendrite formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009019000001_ABST
    Figure 2025009019000001_ABST
Patent Text Reader

Abstract

To provide a nonaqueous electrolyte power storage element having a positive electrode containing a sulfur element and having a large capacity retention rate in a charge / discharge cycle.SOLUTION: A nonaqueous electrolyte power storage element includes a positive electrode containing a sulfur element, a negative electrode having a lithium alloy containing an aluminum element, and a nonaqueous electrolyte containing a fluorinated saturated cyclic carbonate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte electricity storage element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions between the electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used.

[0003] Known non-aqueous electrolyte storage elements include lithium-sulfur batteries (Li-S batteries) and other non-aqueous electrolyte storage elements that use a positive electrode containing elemental sulfur. Patent Document 1 describes a Li-S battery that uses lithium foil as the negative electrode. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-066618 Summary of the Invention [Problem to be solved by the invention]

[0005] Li-S batteries are expected to be a promising energy storage device with high energy density because of the large theoretical capacity of sulfur. However, Li-S batteries have a low capacity retention rate during charge-discharge cycles.

[0006] The present invention has been made in light of the above circumstances, and has an object to provide a nonaqueous electrolyte electricity storage element having a positive electrode containing elemental sulfur, which has a high capacity retention rate during charge-discharge cycles. [Means for solving the problem]

[0007] A nonaqueous electrolyte storage element according to one aspect of the present invention includes a positive electrode containing elemental sulfur, a negative electrode having a lithium alloy containing elemental aluminum, and a nonaqueous electrolyte containing a fluorinated saturated cyclic carbonate. Effect of the Invention

[0008] According to one aspect of the present invention, there is provided a nonaqueous electrolyte electricity storage element including a positive electrode containing elemental sulfur, which has a high capacity retention rate during charge-discharge cycles. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] First, an overview of the nonaqueous electrolyte electricity storage element disclosed in this specification will be described.

[0011] (1) A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode containing elemental sulfur, a negative electrode having a lithium alloy containing elemental aluminum, and a nonaqueous electrolyte containing a fluorinated saturated cyclic carbonate.

[0012] The nonaqueous electrolyte storage element described in (1) above is a nonaqueous electrolyte storage element having a positive electrode containing elemental sulfur, and has a high capacity retention rate during charge-discharge cycles. Although the reason for this is unclear, the following reasons are presumed. The nonaqueous electrolyte storage element described in (1) above includes a positive electrode containing a sulfur element and a negative electrode having a lithium alloy. In the conventional nonaqueous electrolyte storage element, the overvoltage for reducing (precipitating) lithium ions in the negative electrode is large, and therefore the capacity retention rate in the charge-discharge cycle is low. In contrast, the lithium alloy in the negative electrode of the nonaqueous electrolyte storage element described in (1) above contains an aluminum element, and thus the electrical conductivity is improved, and therefore the overvoltage for precipitating lithium ions in the negative electrode (hereinafter also referred to as "precipitating overvoltage") is suppressed. In addition, because the affinity between the lithium element and the aluminum element is high, the crystal structure of the lithium alloy is likely to be maintained homogeneously even if the elution and precipitation of lithium ions are repeated in the charge-discharge cycle. Therefore, the increase in the precipitating overvoltage caused by current concentration and the like and the precipitation of metallic lithium in a dendritic form on the surface of the negative electrode (hereinafter, metallic lithium in a dendritic form is also referred to as "lithium dendrite") are suppressed. Furthermore, the nonaqueous electrolyte of the nonaqueous electrolyte storage element described in (1) above contains a fluorinated saturated cyclic carbonate, so that a good coating film derived from the fluorinated saturated cyclic carbonate is formed on the negative electrode surface. This further suppresses an increase in deposition overvoltage on the negative electrode surface after the coating film is formed. In addition, the growth of lithium dendrites on the negative electrode surface during charge-discharge cycles is suppressed. Therefore, the nonaqueous electrolyte storage element described in (1) above has a high capacity retention rate during charge-discharge cycles.

[0013] The "positive electrode containing elemental sulfur" means, for example, that when the positive electrode has a positive electrode active material layer containing a positive electrode active material, the positive electrode active material layer may contain elemental sulfur, or the positive electrode active material may contain elemental sulfur.

[0014] (2) In the nonaqueous electrolyte storage element described above in (1), the nonaqueous electrolyte may further contain an unsaturated cyclic carbonate.

[0015] In the nonaqueous electrolyte storage element described in (2) above, since the nonaqueous electrolyte further contains an unsaturated cyclic carbonate, a better coating derived from the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate is formed on the negative electrode surface, and therefore the capacity retention rate during charge-discharge cycles is higher.

[0016] (3) In the nonaqueous electrolyte storage element described in (2) above, the volume ratio of the fluorinated saturated cyclic carbonate to the unsaturated cyclic carbonate in the nonaqueous electrolyte (fluorinated saturated cyclic carbonate:unsaturated cyclic carbonate) may be in the range of 10:90 to 99:1.

[0017] In the nonaqueous electrolyte storage element described in (3) above, since the volume ratio of the fluorinated saturated cyclic carbonate to the unsaturated cyclic carbonate is within the above range, a good coating film derived from the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate is more reliably formed on the negative electrode surface, and therefore the capacity retention rate during charge-discharge cycles is higher.

[0018] The "volume ratio of fluorinated saturated cyclic carbonate to unsaturated cyclic carbonate in the nonaqueous electrolyte" is determined from the content of fluorinated saturated cyclic carbonate and unsaturated cyclic carbonate in all nonaqueous solvents in the nonaqueous electrolyte, which is obtained by converting the mass of each nonaqueous solvent measured by gas chromatography mass spectrometry (GC-MS analysis) in accordance with JIS-K-0123 (2018) into a volume at 25°C and 1 atmospheric pressure.

[0019] The volume ratio of the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate in the nonaqueous electrolyte described above is not the volume ratio in the nonaqueous electrolyte used in the production, but the volume ratio in the nonaqueous electrolyte provided in the completed nonaqueous electrolyte storage element. Usually, the nonaqueous electrolyte storage element is completed by assembling an uncharged and discharged nonaqueous electrolyte storage element and then performing an initial discharge and an initial charge (hereinafter also referred to as "initial charge and discharge"). During the initial charge and discharge, a part of the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate is consumed for forming a coating on the negative electrode surface, etc. For this reason, it is considered that the content of the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate in the nonaqueous electrolyte provided in the completed nonaqueous electrolyte storage element is reduced compared to the content of the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate in the nonaqueous electrolyte used in the production. The initial charge and discharge may be performed after assembling an uncharged nonaqueous electrolyte storage element, for example, to check the capacity or to activate a specific positive electrode active material, and refers to the charge and discharge performed before the nonaqueous electrolyte storage element is shipped or used as a completed product. However, the volume ratio of the fluorinated saturated cyclic carbonate to the unsaturated cyclic carbonate in the nonaqueous electrolyte used in the manufacture of the nonaqueous electrolyte storage element tends to be maintained in the nonaqueous electrolyte of the completed nonaqueous electrolyte storage element, so that when the volume ratio for the completed nonaqueous electrolyte storage element is within the above range, the capacity retention rate in the charge and discharge cycle is greater.

[0020] (4) In the nonaqueous electrolyte storage element according to any one of (1) to (3) above, the content of the fluorinated saturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte may be 10% by volume or more and 99% by volume or less.

[0021] In the nonaqueous electrolyte storage element described in (4) above, since the content of the fluorinated saturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is within the above range, a good coating film derived from at least the fluorinated saturated cyclic carbonate is more reliably formed on the negative electrode surface, and therefore the capacity retention rate during charge-discharge cycles is higher.

[0022] The "content of fluorinated saturated cyclic carbonate in the total non-aqueous solvent" is measured by the same GC-MS analysis as described above. As described above, the content of the fluorinated saturated cyclic carbonate in the non-aqueous electrolyte provided in the completed non-aqueous electrolyte storage element is considered to be lower than the content of the fluorinated saturated cyclic carbonate in the non-aqueous electrolyte used in the production. However, if the content of the fluorinated saturated cyclic carbonate remaining in the non-aqueous electrolyte of the completed non-aqueous electrolyte storage element is within the above range, it can be said that the non-aqueous electrolyte used in the production of the non-aqueous electrolyte storage element contained a sufficient amount of the fluorinated saturated cyclic carbonate to form a good coating derived from the fluorinated saturated cyclic carbonate on the negative electrode surface, and in this case, the capacity retention rate in the charge and discharge cycle is also larger.

[0023] (5) In the nonaqueous electrolyte storage element according to any one of (1) to (4) above, the content of the aluminum element in the lithium alloy may be 5% by mass or more and 20% by mass or less.

[0024] In the nonaqueous electrolyte storage element described in (5) above, the content of the aluminum element in the lithium alloy is within the above range, so that the capacity retention rate during charge-discharge cycles is higher.

[0025] The content of each metal element in the lithium alloy contained in the negative electrode is measured by ICP emission spectrometry in accordance with JIS-K-0116 (2014).

[0026] The sample to be measured in the above-mentioned ICP atomic emission spectrometry is collected in the following manner. First, the nonaqueous electrolyte storage element after the initial charge and discharge is charged at a constant current of 0.1C to the charge end voltage during normal use, to be in a charged state. Here, during normal use refers to the case where the nonaqueous electrolyte storage element is used by adopting the charge and discharge conditions recommended or specified for the nonaqueous electrolyte storage element. Next, the nonaqueous electrolyte storage element in this charged state is disassembled, and the positive electrode and the negative electrode are taken out. In addition, the positive electrode and the negative electrode are thoroughly washed with dimethyl carbonate to remove the attached components (nonaqueous electrolyte, etc.), and then dried under reduced pressure at room temperature for 24 hours. Then, the lithium alloy is taken from the negative electrode and used as a sample to be measured for ICP atomic emission spectrometry. In addition, in order to measure the content of lithium element derived from the lithium alloy of the negative electrode that was inserted into the positive electrode and remained after being dissolved from the negative electrode in the nonaqueous electrolyte by the above initial charge and discharge, the positive electrode active material layer taken from the positive electrode is also used as a sample to be measured for ICP atomic emission spectrometry. The content of each metal element in the lithium alloy is the sum of the content of each metal element contained in the lithium alloy extracted from the negative electrode by the above method and the content of lithium element contained in the positive electrode active material layer extracted from the positive electrode. Note that the process from disassembly of the nonaqueous electrolyte storage element to the collection of the measurement sample is carried out in an argon atmosphere with a dew point of -60°C or lower.

[0027] Hereinafter, a nonaqueous electrolyte electricity storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention, and other embodiments will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.

[0028] [Non-aqueous electrolyte energy storage element] A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually of a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked with a separator interposed therebetween, or of a wound type in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween and wound. The nonaqueous electrolyte exists in a state that it is contained in the positive electrode, the negative electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.

[0029] <Positive electrode> The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. In one embodiment of the present invention, the positive electrode contains elemental sulfur as a positive electrode active material, which will be described later.

[0030] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by the volume resistivity being 10 or less, as measured in accordance with JIS-H-0505 (1975). -2 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).

[0031] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0032] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0033] (Cathode active material layer) The positive electrode active material layer contains a positive electrode active material and, if necessary, any optional components such as a conductive agent, a binder, a thickener, and a filler.

[0034] The positive electrode active material layer contains sulfur element as a positive electrode active material. The sulfur element as the positive electrode active material may be simple sulfur or a sulfur compound. Examples of the sulfur compound include metal sulfides such as lithium sulfide, organic disulfide compounds, and organic sulfur compounds such as carbon sulfide compounds. The positive electrode active material containing sulfur element has the advantages of high theoretical capacity and low cost.

[0035] The sulfur element may be in the form of a complex with a conductive agent (a material having higher conductivity than simple sulfur or a sulfur compound). The complex may be in the form in which simple sulfur or a sulfur compound is supported on a conductive agent as a carrier, and specifically, may be a complex of simple sulfur or a sulfur compound and porous carbon (sulfur-porous carbon composite: SPC). The lower limit of the content of the sulfur element in this SPC is preferably 50 mass%, more preferably 60 mass%. Meanwhile, the upper limit of the content is preferably 90 mass%, more preferably 80 mass%. By setting the content of the sulfur element in the SPC to the above range, it is possible to achieve both large electric capacity and good conductivity.

[0036] The lower limit of the content of the sulfur element in the positive electrode active material layer is preferably 40% by mass, more preferably 50% by mass. Meanwhile, the upper limit of this content is preferably 90% by mass, more preferably 70% by mass. When SPC is used, the lower limit of the content of SPC in the positive electrode active material layer is preferably 60% by mass, more preferably 80% by mass. Meanwhile, the upper limit of this content is preferably 95% by mass, more preferably 90% by mass. By setting the content of the sulfur element or SPC within the above range, it is possible to achieve both high electric capacity and good conductivity, and to increase the energy density, etc.

[0037] The positive electrode active material may contain other positive electrode active materials in addition to elemental sulfur, but the lower limit of the content of elemental sulfur or SPC in the entire positive electrode active material is preferably 50 mass%, more preferably 90 mass%, and even more preferably 99 mass%.

[0038] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0039] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferred from the viewpoint of electronic conductivity and coatability, and acetylene black is preferred among them. The conductive agent may be in the form of a complex with the above-mentioned sulfur element, or in a form other than the complex with the sulfur element. That is, for example, the positive electrode active material layer may contain a conductive agent that constitutes the SPC and other conductive agents other than the conductive agent.

[0040] The content of the conductive agent (excluding the above-mentioned complex with sulfur element) in the positive electrode active material layer is preferably 1 mass% or more and 15 mass% or less, more preferably 1.5 mass% or more and 10 mass% or less. By setting the content of the conductive agent in the above range, the energy density of the nonaqueous electrolyte storage element can be increased.

[0041] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0042] The content of the binder in the positive electrode active material layer is preferably from 1% by mass to 10% by mass, and more preferably from 3% by mass to 9% by mass. By setting the content of the binder in the above range, the positive electrode active material can be stably maintained.

[0043] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. In one embodiment of the present invention, it may be preferable that the thickener is not contained in the positive electrode active material layer.

[0044] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and their artificial products. In one embodiment of the present invention, it may be preferable that the filler is not contained in the positive electrode active material layer.

[0045] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0046] <Negative electrode> The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode. In one embodiment of the present invention, the negative electrode has a lithium alloy containing an aluminum element as a negative electrode active material described later.

[0047] The negative electrode substrate has electrical conductivity. The material of the negative electrode substrate may be copper, nickel, stainless steel, nickel-plated steel, carbonaceous material, or the like. Among these, nickel or nickel alloy is preferred. The negative electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, or the like, and from the viewpoint of cost, a foil is preferred. Therefore, the negative electrode substrate is preferably a nickel foil or a nickel alloy foil. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0048] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0049] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, a filler, etc., as necessary. The optional components such as a conductive agent, a binder, a thickener, a filler, etc. can be selected from the materials exemplified for the positive electrode above.

[0050] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0051] The negative electrode active material layer contains a lithium alloy containing an aluminum element as a negative electrode active material. The lithium alloy is, for example, a solid solution of lithium element and aluminum element.

[0052] The lithium alloy is preferably composed of lithium and aluminum. In this case, the lithium alloy may contain typical elements and transition metal elements other than lithium and aluminum as inevitable impurities, but is preferably composed substantially of lithium and aluminum. Here, "substantially" means that the content of inevitable impurities is 1 mass% or less.

[0053] The lower limit of the content of the aluminum element in the lithium alloy is preferably 5% by mass, more preferably 8% by mass, and even more preferably 10% by mass. On the other hand, the upper limit of the content of the aluminum element in the lithium alloy is preferably 25% by mass, more preferably 22% by mass, and even more preferably 20% by mass. When the content of the aluminum element in the lithium alloy is equal to or more than the above lower limit, the crystal structure of the lithium alloy is easily maintained homogeneously even if the elution and precipitation of lithium ions are repeated in the charge and discharge cycle. In addition, when the content of the aluminum element in the lithium alloy is equal to or less than the above upper limit, the lithium alloy can be easily manufactured. The content of the aluminum element in the lithium alloy can be equal to or more than any of the above lower limits and equal to or less than any of the above upper limits.

[0054] The negative electrode active material may contain other negative electrode active materials than the lithium alloy, but the content of the lithium alloy in the total negative electrode active material is preferably 50% by mass or more and 100% by mass or less, more preferably 90% by mass or more and 100% by mass or less, and even more preferably 99% by mass or more and 100% by mass or less.

[0055] The negative electrode active material other than the lithium alloy can be appropriately selected from known negative electrode active materials. Examples of the negative electrode active material other than the lithium alloy include metals or semi-metals such as Si and Sn; metal oxides or semi-metal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO 2、 Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon). In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0056] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0057] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0058] Here, the "discharged state" of the carbon material means a state in which the carbon material, which is the negative electrode active material, is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released. For example, in a single-electrode battery using a negative electrode containing a carbon material as the negative electrode active material as a working electrode and metallic Li as a counter electrode, the state is one in which the open circuit voltage is 0.7 V or more.

[0059] "Non-graphitizable carbon" means the above d 002This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0060] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0061] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass or more and 100% by mass or less, and more preferably 90% by mass or more and 100% by mass or less. By setting the content of the negative electrode active material in the above range, it is possible to achieve both high energy density and manufacturability of the negative electrode active material layer. When the negative electrode active material is composed of only a lithium alloy, the content of the negative electrode active material in the negative electrode active material layer may be 99% by mass or more, or may be 100% by mass.

[0062] The negative electrode active material layer may be a non-porous layer (solid layer) or a porous layer, but is preferably a non-porous layer. The negative electrode active material layer may be a lithium alloy layer. The average thickness of the negative electrode active material layer is preferably 5 μm to 1,000 μm, more preferably 10 μm to 500 μm, and even more preferably 30 μm to 300 μm.

[0063] <separator> The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0064] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the nonaqueous electrolyte storage element.

[0065] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0066] As the separator, a polymer gel composed of a polymer and an electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0067] <Non-aqueous electrolyte> The non-aqueous electrolyte may be a non-aqueous electrolytic solution that contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.

[0068] The non-aqueous solvent contains a fluorinated saturated cyclic carbonate. When the non-aqueous solvent contains a fluorinated saturated cyclic carbonate in this manner, a good coating derived from the fluorinated saturated cyclic carbonate can be formed on the surface of the negative electrode.

[0069] The non-aqueous solvent preferably further contains an unsaturated cyclic carbonate. By further containing the unsaturated cyclic carbonate, the non-aqueous solvent can form a better coating film derived from the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate on the negative electrode surface.

[0070] The fluorinated saturated cyclic carbonate may be a cyclic carbonate that does not contain an unsaturated bond in the ring structure and in which some of the hydrogen atoms in the ring structure or the hydrogen atoms in the hydrocarbon group are substituted with fluorine. The number of ring members in the ring structure of the fluorinated saturated cyclic carbonate is preferably 3 to 8, more preferably 4 to 6, and even more preferably 5.

[0071] Examples of the fluorinated saturated cyclic carbonate include fluorinated ethylene carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC), fluorinated propylene carbonate, and fluorinated butylene carbonate. Among these, FEC or DFEC is preferred, and FEC is more preferred.

[0072] The unsaturated cyclic carbonate may be a cyclic carbonate containing an unsaturated bond in the ring structure, or may be a cyclic carbonate containing a carbon-carbon double bond in the ring structure. The number of ring members in the ring structure of the unsaturated cyclic carbonate is preferably 3 to 8, more preferably 4 to 6, and even more preferably 5. In addition, the unsaturated cyclic carbonate may be one in which some of the hydrogen atoms are replaced by halogen, but it is preferable that the hydrogen atoms are not replaced by halogen.

[0073] Examples of the unsaturated cyclic carbonate include vinylene carbonate (VC), methylvinylene carbonate, ethylvinylene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, vinylethylene carbonate (VEC), styrene carbonate, etc. Among these, VC is preferred.

[0074] The non-aqueous solvent may contain a non-aqueous solvent other than the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate. Examples of the non-aqueous solvent include linear carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are replaced with halogens may be used. As the non-aqueous solvent, a saturated cyclic carbonate that does not have a fluorine atom may be used.

[0075] Examples of the saturated cyclic carbonate not containing a fluorine atom include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and chloroethylene carbonate.

[0076] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, and bis(trifluoroethyl) carbonate.

[0077] The volume ratio of the fluorinated saturated cyclic carbonate to the unsaturated cyclic carbonate (fluorinated saturated cyclic carbonate:unsaturated cyclic carbonate) is preferably in the range of 10:90 to 99:1, more preferably in the range of 20:80 to 99:1, even more preferably in the range of 30:70 to 99:1, even more preferably in the range of 40:60 to 99:1, and particularly preferably in the range of 50:50 to 99:1. By having the volume ratio of the fluorinated saturated cyclic carbonate to the unsaturated cyclic carbonate within the above range, the coating formed on the negative electrode surface contains components derived from the fluorinated saturated cyclic carbonate and the unsaturated cyclic carbonate, and the capacity retention rate during charge and discharge cycles can be increased.

[0078] The lower limit of the content of the fluorinated saturated cyclic carbonate in the total non-aqueous solvent is preferably 10% by volume, more preferably 20% by volume, even more preferably 30% by volume, even more preferably 40% by volume, and particularly preferably 50% by volume. When the content of the fluorinated saturated cyclic carbonate is equal to or more than the lower limit, the coating formed on the negative electrode surface contains a component derived from the fluorinated saturated cyclic carbonate, and the capacity retention rate during charge and discharge cycles can be increased. On the other hand, the upper limit of the content of the fluorinated saturated cyclic carbonate in the total non-aqueous solvent may be, for example, 100% by volume or 99% by volume.

[0079] The lower limit of the content of the unsaturated cyclic carbonate in the total non-aqueous solvent may be 0 vol%, or may be 1 vol%. On the other hand, the upper limit of the content of the unsaturated cyclic carbonate in the total non-aqueous solvent is preferably 90 vol%, more preferably 80 vol%, even more preferably 70 vol%, even more preferably 60 vol%, and particularly preferably 50 vol%. When the content of the unsaturated cyclic carbonate is equal to or more than the lower limit and equal to or less than the upper limit, the coating formed on the negative electrode surface contains a component derived from the unsaturated cyclic carbonate, and the capacity retention rate during charge-discharge cycles can be increased.

[0080] The electrolyte salt may be a lithium salt.

[0081] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts and lithium salts having a halogenated hydrocarbon group are preferred, and LiN(SO2CF3)2 is more preferred.

[0082] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0083] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of additives include oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, Itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, and the like. These additives may be used alone or in combination of two or more.

[0084] The content of the additive contained in the nonaqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or the charge / discharge cycle performance after high-temperature storage, and to further improve safety.

[0085] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery. Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0086] [Electricity storage device] The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements 1 assembled together in an automobile power source such as an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc., a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, the technology of the present invention may be applied to at least one nonaqueous electrolyte storage element included in the electricity storage unit. 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.

[0087] [Method of manufacturing non-aqueous electrolyte storage element] A method for manufacturing a nonaqueous electrolyte storage element according to one embodiment of the present invention includes preparing a positive electrode containing elemental sulfur, preparing a negative electrode having a lithium alloy containing elemental aluminum, and preparing a nonaqueous electrolyte containing a fluorinated saturated cyclic carbonate.

[0088] The method for manufacturing the nonaqueous electrolyte storage element includes, as other steps, preparing an electrode body and housing the electrode body and the nonaqueous electrolyte in a container. Preparing the electrode body may be, for example, forming an electrode body by stacking or winding the positive electrode and the negative electrode via a separator. The specific configurations of the positive electrode, the negative electrode, the separator, and the nonaqueous electrolyte are as described above in the embodiment of the nonaqueous electrolyte storage element. The above configuration is applied in the process of manufacturing the nonaqueous electrolyte storage element, not in the completed nonaqueous electrolyte storage element.

[0089] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.

[0090] [Other embodiments] The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0091] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium-sulfur battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors.

[0092] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES

[0093] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0094] [Example 1] (Preparation of positive electrode) Sulfur and porous carbon were mixed in a mass ratio of 70:30. This mixture was placed in a sealed reaction vessel, which was then placed in a sealed electric furnace. After argon flow for 1 hour, the mixture was heated to 150°C at a rate of 5°C / min and held for 5 hours, then allowed to cool to 80°C, the temperature at which sulfur solidifies, and then heated again to 300°C at a rate of 5°C / min and held for 2 hours to produce a sulfur-porous carbon composite (SPC).

[0095] A positive electrode mixture paste containing the above-mentioned sulfur-porous carbon composite (SPC), acetylene black as a conductive agent, single-walled carbon nanotubes as a conductive agent, CMC as a thickener, PAA as a binder, and SBR as a binder, using water as a dispersion medium, was applied to one side of a positive electrode substrate made of aluminum foil and dried to prepare a positive electrode.

[0096] (Preparation of negative electrode) A sheet-shaped lithium alloy (average thickness 300 μm) was laminated as a negative electrode active material layer on one side of nickel foil, which was the negative electrode substrate, and pressed. The lithium alloy was formed by dissolving metallic lithium with metallic aluminum as another metal at a content of 20 mass% (the mass ratio of lithium element and aluminum element in the lithium alloy foil (lithium element:aluminum element) was 80:20). In this way, a negative electrode in which a negative electrode active material layer was laminated on one side of the negative electrode substrate was produced.

[0097] (Preparation of non-aqueous electrolyte) A non-aqueous solvent consisting of a mixture of fluoroethylene carbonate (FEC) and vinylene carbonate (VC) in a volume ratio of 50:50 was added to the electrolyte salt LiTFSI (LiN(SO2CF3)2) at a concentration of 1.0 mol / dm 3 The above solution was used as a non-aqueous electrolyte.

[0098] (Fabrication of non-aqueous electrolyte storage element) A single-layer electrode body was obtained using a positive electrode, a negative electrode, and a polyolefin porous resin film as a separator. The electrode body was placed in a container, and a nonaqueous electrolyte was poured into and sealed to obtain a nonaqueous electrolyte storage element of Example 1.

[0099] [Comparative Examples 1 to 11] In the lithium alloy of the negative electrode active material layer, the type and content of other metals dissolved in metallic lithium were as shown in Table 1, and a nonaqueous solvent containing 100% by volume of vinylene carbonate (VC) was used for the nonaqueous electrolyte. The nonaqueous electrolyte storage elements of Comparative Examples 1 to 11 were obtained in the same manner as in Example 1. In addition, the content of unavoidable impurities in the lithium alloy of each Example and Comparative Example was 1% by mass or less. In addition, "-" in the "other metals" and "content" columns in Table 1 means that other metals dissolved in metallic lithium are substantially absent, and the negative electrode active material layer at this time is pure metallic lithium. The content of unavoidable impurities in the above pure metallic lithium was also 1% by mass or less.

[0100] [Example 2 and Comparative Examples 12 to 20] Non-aqueous electrolyte storage elements of Example 2 and Comparative Examples 12 to 20 were obtained in the same manner as in Example 1, except that in the lithium alloy of the negative electrode active material layer, the type and content of other metals dissolved in metallic lithium were as shown in Table 1.

[0101] [evaluation] For each of the obtained nonaqueous electrolyte storage elements, a constant current discharge was performed at 25°C to 1V at a current of 0.1C as the first discharge. After the discharge, a constant current constant voltage charge was performed at 25°C to 3V at a current of 0.1C until the total charging time was 30 hours. Then, a second discharge and charge were performed in the same manner as above (initial capacity confirmation test). After that, the same discharge and charge process as above was defined as one cycle, and this cycle was repeated 10 times (charge and discharge cycle life test). In addition, a 10-minute pause was provided at 25°C after each discharge and charge. Discharge, charge and pause were all performed in a thermostatic chamber at 25°C. Table 1 shows the "capacity retention rate after 1 cycle" obtained by dividing the discharge capacity at the first discharge in the charge and discharge cycle life test by the discharge capacity at the second discharge in the initial capacity confirmation test, and the "capacity retention rate after 10 cycles" obtained by dividing the discharge capacity at the 10th discharge in the charge and discharge cycle life test by the discharge capacity at the second discharge in the initial capacity confirmation test. In addition, in Table 1, a "-" in the column of "Capacity maintenance rate" means that the nonaqueous electrolyte storage element is short-circuited.

[0102] [Table 1]

[0103] As shown in Table 1, Comparative Examples 1 to 11 in which the nonaqueous electrolyte solvent contained only VC short-circuited before the 10th cycle. On the other hand, except for Comparative Examples 12 and 13 in which the lithium alloy of the negative electrode contained magnesium element, when the nonaqueous electrolyte solvent contained FEC, i.e., Examples 1 and 2 and Comparative Examples 14 to 20, no short-circuit occurred even after 10 cycles. This suggests that the nonaqueous solvent containing FEC provided a good coating to protect the negative electrode surface.

[0104] Examples 1 and 2, in which the lithium alloy of the negative electrode contained aluminum element and the nonaqueous solvent of the nonaqueous electrolyte contained FEC, both had a higher capacity retention rate after 10 cycles than Comparative Examples 14 to 19 in which the lithium alloy of the negative electrode contained elements other than aluminum element and Comparative Example 20 in which pure metallic lithium was used for the negative electrode. This shows that the capacity retention rate during charge and discharge cycles is increased by the synergistic effect of the lithium alloy of the negative electrode containing aluminum element and the nonaqueous solvent of the nonaqueous electrolyte containing FEC. [Industrial Applicability]

[0105] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0106] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. A positive electrode containing elemental sulfur; a negative electrode having a lithium alloy containing an aluminum element; a non-aqueous electrolyte containing a fluorinated saturated cyclic carbonate; A non-aqueous electrolyte electricity storage element comprising:

2. 2. The nonaqueous electrolyte storage element according to claim 1, wherein the nonaqueous electrolyte further contains an unsaturated cyclic carbonate.

3. 3. The nonaqueous electrolyte storage element according to claim 2, wherein the volume ratio of the fluorinated saturated cyclic carbonate to the unsaturated cyclic carbonate in the nonaqueous electrolyte (fluorinated saturated cyclic carbonate:unsaturated cyclic carbonate) is in the range of 10:90 to 99:

1.

4. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the fluorinated saturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is 10% by volume or more and 99% by volume or less.

5. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the aluminum element in the lithium alloy is from 5% by mass to 20% by mass.

Citation Information

Patent Citations

  • Porous carbon material, method for producing porous carbon material, complex, method for producing complex, positive electrode for lithium sulfur battery, and lithium sulfur battery

    JP2021066618A